Top 10 global educational topics in stroke: A survey by the World Stroke Organization. Issue 8 (October 2019) - Saini, Monica; Belson, Sarah; Lahiff-Jenkins, Carmen; Sandercock, Peter
Aim: As part of a program of work to develop an educational strategy and implementation plan for the World Stroke Organization, we conducted a survey of World Stroke Organization members (health professionals, laypersons (Stroke Support Organizations)) to identify their potential educational needs. Methods: We developed a questionnaire to identify priority educational needs in consultation with the World Stroke Organization Education Committee. The World Stroke Organization invited all individual members and associated Stroke Support Organizations to complete the questionnaire via a web-based survey. Survey responses were supplemented by questionnaires emailed directly to key persons in Stroke Support Organizations and information from semi-structured telephone interviews, where necessary. The questionnaire asked respondents to prioritize topics in diagnosis, management of acute stroke, stroke care services, stroke rehabilitation, and stroke prevention. Free-text responses were assessed with word cloud. Results: The online survey was completed by 264 respondents from 60 countries; 19.1% were from low- and middle-income countries, 59% were stroke specialist physicians, 28% allied health professionals or nurses, 9% Stroke Support Organizations, 4% general physicians. Fifteen Stroke Support Organizations from 11 countries responded to the emailed survey. Seven Stroke Support Organizations' members were interviewed by telephone; one was interviewed in-person. We highlight the two highest priority topics in each of the five questionnaire domains. Conclusion: The 10 priority topics were all applicable in a low- or middle-income setting: setting up and delivering stroke diagnosis, treatment, rehabilitation and prevention services, and emphasized the most basic elements of care. The survey participants have identified a number of key topics that merit inclusion in stroke teaching materials and courses, especially those aimed at practitioners working in resource-limited settings.